Implementation of a calibration algorithm for efficient modeling of direction-dependent and baseline-dependent effects for interferometric imaging arrays in radio astronomy - Hokwana, Anathi (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.